Environmental factors affecting living comfort perception in different localities in Sri Lanka - Mohamed Gazzaly Mohamed Thariq; Najim Mohamed Mujithaba Mohamed (TeMA: Journal of Land Use, Mobility and Environment)
The living in comfort and the consequent healthier life is a reaction to the environment indicated by the absence of environmental stressors. The present study investigated the factors influencing the living comfort perception in an urban and a non-urban locality in Sri Lanka.  A survey using a pre-tested questionnaire was carried out to solicit the people’s perceptions on identified environmental factors randomly selecting fifty households from each locality. The results showed the factors i.e., stray animals, dust and garbage negatively affected living comfort in both urban and non-urban localities while temperature, insects, flood, noise, smoke, vibration, and bad odor negatively affected living comfort in the urban locality. Further, the factors i.e., rainfall, wind, humidity and drinking water were not important for living comfort perception in both localities. The factors i.e., water bodies, space, natural beauty, and biodiversity affected the living comfort positively in the urban locality. The factors identified in this study are useful in zoning the localities according to their suitability in relation to public comfort perception. Further, the identified factors can be manipulated to improve the living comfort perception in urban and non-urban localities.